Corona virus pandemic: current scenario and future hopes - Sharma, Awadhesh Kumar (International Journal of Research in Medical Sciences, 2020)
Whenever we human beings challenge the existence of the god or tried to prove ourselves superior to the nature. The Nature bounces back in the form of these pandemics of infectious disease which forced us to either surrender or to lockdown ourselves in homes. The current outbreak of Corona Virus Disease-19 (COVID-19) is the same warning from nature. It is spreading very fast from one country to other and almost affects the whole world. We have many unanswered questions. Currently in absence of any definitive treatment, prevention is an only option. But future hopes are still there. This article gives a brief and accurate detail of COVID-19 pandemic regarding current situation and future hopes.